MENINGKATKAN EFEKTIVITAS KERJA DOSEN MELALUI PENJAMINAN MUTU DAN EFIKASI DIRI - Santa Manurung (Poltekkes Kemenkes Jakarta III, 2016)
Effectiveness refers to the intervention’s ability to do more good than harm for the target population in a real world setting. The research is conducted at HealthPolytechnic of Ministry of Health Jakarta III to obtain information on the effect of quality assurance, self-efficacy towards lecturers’ job effectiveness. The research used 60 out of 145 lecturers as the population selected using simple random sampling. The research is conducted by using a method of causal with path analysis. The result of the research showed that: (1). there is direct effect quality assurance on lecturers’ job effectiveness; (2). there is direct effect of self-efficacy on lecturers’ job effectiveness, and (3). there is direct effect of quality assurance on self-efficacy.Therefore, jobeffectiveness of Health Polytechnic lecturer of Ministry of Health Jakarta III can be enhanced by carrying out quality assurance and self-efficacy